(untitled) - Smith, Thomas C. (Stanford, 1983)
Contents: The beginnings of modern industry; Political change and technological innovation; Motivation; Private versus government enterprise; Government enterprises...
Keywords: Ngành công nghiệp,Industries; Nhật Bản,Japan